The Mediating Role of Work Engagement in the Effect of Leader-Member Exchange on Job Performance - ÖZBEZEK, B. Dilek; EGE, Tayfur (Yonetim ve Ekonomi Arastirmalari Dergisi - Journal of Management and Economics Research, 2022)
Today, in order for businesses to sustain their presence and gain a competitive advantage in the sector in which they operate, their employees must be able to achieve a high level of performance consistently. Although there are many factors affecting job performance, a leader-member exchange is an important concept used to explain the relationship between manager and employee. This study aims to determine to what extent leader-member exchange affects job performance levels and to determine the mediating role of work engagement in this interaction. The research population of this study consists of business employees operating in the textile sector in Gaziantep 5th Organized Industrial Region. The sample size reached for this study is 284 participants. The data obtained from the participants by the face-to-face survey was tested by performing explanatory and confirmatory factor analysis, descriptive statistics, correlation, and bootstrap regression analysis. The results of conceptual and empirical studies clearly show that there is a statistically significant relation between leader-member exchange and job performance. However, work engagement has a partial mediating role in the relation between job performance and leader-member exchange.
Keywords: Job Performance Leader-Member Exchange.; Work Engagement; Job Performance; 8. Economic growth